Evaluasi Unjuk Kerja Routing Link-State Pada Jaringan Packet Switched Menggunakan NS-2 (Network Simulator–2) - Sukiswo, Sukiswo (Transmisi, 2008)
Routing is processing to find route from source to destination in communication network Data from source to destination will be delivered from one node to other node and need the best route. The best route is the shortest path with minimum cost and connected with other path. Routing become  important for delivered data from source node  to destination node. Link-State is one of routing algoritm  being used in packet switched network. Link-State will calculate the best route and keep the result for data base in router. After calculation will beknow the best route with minimum link-cost  for destination.In this final project will be shown the routing simulation with Link-State routing protocol used NS–2 (Network Simulor–2), the simulation software for communication network. The network use different number of router, that is twenty routers, thirty routers, fourty routers, and  fifty routers. From simulation the performance will be analized from Link-State routing protocol in the packet switched network. The performance measurement is throughput, packet loss, and delay. The network use fourty routers showing the best performance for the network which simulated in this final project. Keywords :  routing, packet-switched, link-state, node, link, NS  – 2, link-cost, throughput, packet loss, and delay